Mechanosensitive Piezo1 protein as a novel regulator in macrophages and macrophage-mediated inflammatory diseases - Tang, Yu; Zhao, Chuanxiang; Zhuang, Ying; Zhong, Anjing; Wang, Ming; Zhang, Wei; Zhu, Liqun (Frontiers in Immunology, 2023)
Macrophages are the most important innate immune cells in humans. They are almost ubiquitous in peripheral tissues with a large variety of different mechanical milieus. Therefore, it is not inconceivable that mechanical stimuli have effects on macrophages. Emerging as key molecular detectors of mechanical stress, the function of Piezo channels in macrophages is becoming attractive. In this review, we addressed the architecture, activation mechanisms, biological functions, and pharmacological regulation of the Piezo1 channel and review the research advancements in functions of Piezo1 channels in macrophages and macrophage-mediated inflammatory diseases as well as the potential mechanisms involved.